2018
DOI: 10.1016/j.arth.2018.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Survival and Good Outcomes at 15 Years Using the Press-Fit Condylar Sigma Total Knee Arthroplasty

Abstract: The Press-Fit Condylar Sigma total knee arthroplasty represents a durable, effective option for patients undergoing knee arthroplasty, with excellent survival and good clinical and radiographic outcomes at 15 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…Comparison with the literature is difficult because no other studies have analyzed TKA following ipsilateral THA. The functional outcomes of TKA in the present study, as measured by the KSS, were comparable to those of the most recent studies published [9, 11, 16, 17]. Likewise, the survival in the present study for ipsilateral TKA following prior THA was comparable to that of other recent studies [5, 9, 11, 13, 16] in which TKA survival ranged between 92 and 98% at 8–15 years was reported.…”
Section: Discussionsupporting
confidence: 87%
“…Comparison with the literature is difficult because no other studies have analyzed TKA following ipsilateral THA. The functional outcomes of TKA in the present study, as measured by the KSS, were comparable to those of the most recent studies published [9, 11, 16, 17]. Likewise, the survival in the present study for ipsilateral TKA following prior THA was comparable to that of other recent studies [5, 9, 11, 13, 16] in which TKA survival ranged between 92 and 98% at 8–15 years was reported.…”
Section: Discussionsupporting
confidence: 87%
“…Pooled analysis of data derived from case series reported at exactly 15 years or 20 years showed an all-cause construct survivorship of 96·3% (95% CI 95·7–96·9) at 15 years and 94·8% (92·5–97·1) at 20 years. Figure 2A shows a forest plot for the meta-analysis of data on TKRs derived from case series at 15 years and 20 years.
Figure 2Forest plot of estimates for reported survival of knee replacements from case series11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32(A) Total knee replacements at 15 years and 20 years. (B) Unicondylar knee replacements at 15 years, 20 years, and 25 years.
…”
Section: Resultsmentioning
confidence: 99%
“…Total knee arthroplasty (TKA) is an orthopedic surgical approach that is widely applied for patients with severely painful joint diseases (e.g., degenerative arthritis, inflammatory arthritis, and avascular necrosis), with a high success rate of >90%. TKA survival rates reportedly exceed 95% at 10 years and 90% at 15 years [1,2]. The Fourth American Joint Replacement Registry reported that TKAs were performed for approximately 0.5 million people in the USA in 2016 and will be performed in approximately 3 million people annually worldwide after 2030 [3][4][5].…”
Section: Introductionmentioning
confidence: 99%